2022
DOI: 10.1111/ijfs.15676
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polar compounds distribution in deep‐frying oil on lipid digestion behaviour

Abstract: Deep-frying oil featuring total polar compound (TPC) has been found to be unhealthy. However, little information is available regarding the impact of TPC on the lipid digestion behaviour. In this study, three typical edible oils (palm oil, PO; high oleic acid peanut oil, HOA; and high linoleic acid sunflower oil, HLA) were selected to investigate the effect of deep-frying on the lipid digestion. Digestion behaviour was monitored by pH-Stat method in vitro. Digestibility rate analysis showed that free fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…After gastric digestion, the lipid droplet size of the emulsion increases significantly, and the lipid particle diameter gradually decreases in the digestive phase of the small intestine. Many studies have revealed why samples undergo changes during the oral, gastric, and intestinal stages [13] , [23] . After oral digestion, the mean particle diameter of the lipid emulsion droplets increased, indicating that salivary mucin in simulated oral fluid may cause aggregation and bridging of fat emulsion droplets [24] .…”
Section: Resultsmentioning
confidence: 99%
“…After gastric digestion, the lipid droplet size of the emulsion increases significantly, and the lipid particle diameter gradually decreases in the digestive phase of the small intestine. Many studies have revealed why samples undergo changes during the oral, gastric, and intestinal stages [13] , [23] . After oral digestion, the mean particle diameter of the lipid emulsion droplets increased, indicating that salivary mucin in simulated oral fluid may cause aggregation and bridging of fat emulsion droplets [24] .…”
Section: Resultsmentioning
confidence: 99%
“…These studies have shown that TIOO can cause adverse health effects, including intestinal barrier disturbance, liver damage, and lipid metabolism imbalance in multiple organs. [16][17][18] Nevertheless, the neurological effects of TIOO have not been studied.…”
Section: Introductionmentioning
confidence: 99%